DETERMINANT MODEL OF JOB SATISFACTION AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Farisi, Salman; Lubis, Saidan Sany; Sudirman, Acai; Nurhayati, Nurhayati (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2025)
This research aims to determine the influence of Person Job Fit and Person Organizational Fit on Organizational Citizenship Behavior through Job Satisfaction as an Intervening Variable at the Directors' Office of PT Perkebunan Nusantara IV Regional I Medan, both directly and indirectly. This research used a quantitative approach with a sample size of 86 people. A questionnaire was used for data collection in this research. The data analysis technique uses Partial Least Square - Structural Equestion Model (PLS-SEM), which aims to conduct path analysis using latent variables. The research results show that Person Job Fit has an effect on Organisational Citizenship Behaviour, Person Organisational Fit affects Organisational Citizenship Behaviour, and Person Job Fit has no effect on Job Satisfaction. Personal Organizational Fit influences employee job satisfaction. Job satisfaction influences employee Organizational Citizenship Behavior. Person Job Fit does not affect Organizational Citizenship Behavior through PT Employee Job Satisfaction. Perkebunan Nusantara IV Regional I Medan. Personal Organizational Fit influences Organizational Citizenship Behavior through PT Employee Job Satisfaction. Perkebunan Nusantara IV Regional I Medan.